Assessment of role of burden in caregivers of substance abusers: a study done at Swami Vivekananda Drug De-addiction Centre, Govt. Medical College, Amritsar - Kaur, Arshdeep; Mahajan, Sanjeev; Deepti, Shyam Sunder; Singh, Tejbir (International Journal Of Community Medicine And Public Health, 2018)
Background: Substance abuse is a multidimensional problem, which threatens the quality of life of not only substance abusers but also the family members who live with them. Most of the time a member of the family assumes the role of caregiver and he or she is most burdened from this process. Considering that the involvement of family members is recommended for the recovery process of chemical dependents, it is necessary to appropriately provide the training to caregivers and evaluate their needs for caregiving. Methods: This cross sectional study was conducted at Swami Vivekananda Drug De-addiction Centre attached to the Government Medical College, Amritsar from January 2016 to December 2016. A total of 349 caregivers of substance abusers were interviewed by using pretested and semi structured questionnaire. Results: 44.69% caregivers were wives. Mean age of the caregiver was 33.45 years. 25.21% were high pass. 67.6% were housewives. None was trained in caregiving professionally. 37.53% provided family care while emotional support to the patients was provided by only 10% women and 2% men, no gender specific association with emotional support was statistically significant. 54.15% developed stress while caregiving, 12.60% had social and financial problems. Conclusions: Findings confirmed that quality of life is compromised and stress is high among caregivers, highlighting the need for providing emotional support.